The use of novel diagnostics to individualize immunosuppression following transplantation. (4th February 2015) - Schlickeiser, Stephan; Boës, David; Streitz, Mathias; Sawitzki, Birgit
Summary Despite major improvements in short‐term survival of organ allografts, long‐term graft survival has not changed significantly. It is also known that toxic side effects of current immunosuppressive drugs (IS) especially calcineurin inhibitors (CNI) contribute to the unsatisfactory graft and patient survival following transplantation. Thus, clinicians strive to reduce or wean IS in potentially eligible patients. Research in the last 10 years has focussed on identification of biomarkers suitable for patient stratification in minimization or weaning trials. Most of the described biomarkers have been run retrospectively on samples collected within single‐centre trials. Thus, often their performance has not been validated in other potentially multicentre clinical trials. Ultimately, the utility of biomarkers to identify potential weaning candidates should be investigated in large randomized prospective trials. In particular, for testing in such trials, we need more information about the accuracy, reproducibility, stability and limitations of the described biomarkers. Also, data repositories summarizing crucial information on biomarker performance in age‐ and gender‐matched healthy individuals of different ethnicity are missing. This together with improved bioinformatics tools might help in developing better scores for patient stratification. Here, we will summarize the current results, knowledge and limitations on biomarkers for drug minimization or weaning trials.